High-gloss and high-mechanical-strength PC / ASA composite material and preparation method thereof

By adjusting the proportion of PC resin and adding appropriate amounts of ASA glue powder, SAN resin and other components, the problems of impact resistance and photooxygen aging in automotive exterior parts are solved, and PC/ASA composite materials with high gloss, high mechanical strength and photooxygen aging are achieved.

CN119592040APending Publication Date: 2025-03-11ZHONGSHAN HUABANG PLASTICS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411931854.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing PC/ASA alloy materials have poor impact resistance in automotive exterior parts and lack ultraviolet absorbers, which may aging when exposed to light outdoors for a long time.

Method used

Using high gloss and high mechanical strength PC/ASA composite material, the mechanical properties and photooxygen aging ability of the material are improved by adjusting the ratio of PC resin 1 and PC resin 2, combining ASA glue powder, SAN resin, PMMA resin, composite antioxidant, lubricant, compatible agent, SAN carrier black masterbatch and ultraviolet absorber.

Benefits of technology

It realizes the high mechanical properties and high gloss appearance of PC/ASA composite materials, which can meet the visual needs of automotive exterior parts, and also has good impact resistance and photooxygen aging resistance, extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210531170000071
    Figure BDA0005210531170000071
  • Figure BDA0005210531170000081
    Figure BDA0005210531170000081
Patent Text Reader

Abstract

The invention discloses a high-gloss and high-mechanical-strength PC / ASA composite material and a preparation method thereof. The PC / ASA composite material is prepared from the following raw materials in parts by mass: 40 to 60 parts of PC resin 1, 10 to 30 parts of PC resin 2, 5 to 10 parts of ASA rubber powder, 15 to 30 parts of SAN resin, 2 to 9 parts of PMMA resin, 0.1 to 0.5 part of compound antioxidant, 0.4 to 0.8 part of lubricant, 0.5 to 1.5 parts of compatilizer, 2 to 4 parts of SAN carrier black master batch and 0.1 to 0.5 part of ultraviolet light absorber. Under the conditions of 300 DEG C and 1.2 kg load, the melt index of the PC resin 1 is 8-14 g / 10 min, and the melt index of the PC resin 2 is 18-24 g / 10 min. The prepared high-gloss and high-mechanical-strength PC / ASA composite material has excellent mechanical properties and light-oxygen aging resistance, and the condition that the PC / ASA composite material is uneven is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer material, a PC / ASA composite material with high gloss and high mechanical strength and a preparation method thereof. Background Art

[0002] In the prior art, automobile exterior parts, such as the housing of automobile lamps, are usually injection molded by polymer materials. Since automobile exterior parts are installed on the outside of the car, they need to have a good bright appearance to meet the visual needs of customers, and also need good toughness and impact resistance to prevent deformation. Currently, the polymer materials used for injection molding of automobile exterior parts are mainly PC, PMMA, and ASA, and other components are added to improve the comprehensive performance of the materials.

[0003] For example, a Chinese patent with publication number CN105885379A discloses a scratch-resistant, high-gloss, spray-free PC / ASA alloy material, including the following components in parts by weight: 50 to 70 parts of PC resin, 10-40 parts of ASA resin, 5 to 20 parts of scratch-resistant agent, 0.1 to 1 part of compatibilizer, 0.1 to 1 part of antioxidant, 0.1 to 1 part of lubricant, and 2 to 5 parts of carbon black masterbatch. The relative molecular weight of the PC resin as the main body of the alloy material is 15,000 to 30,000 g / mol, which has good fluidity and processing performance, but relatively poor heat resistance and impact resistance, resulting in poor impact resistance of automobile exterior parts made of PC / ASA alloy material. In addition, the alloy material does not have an ultraviolet absorber and may be easily aged if exposed to light outdoors for a long time.

[0004] In view of this, the present invention proposes a high-gloss, high-mechanical-strength PC / ASA composite material and a preparation method and application thereof to solve the above-mentioned problems. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned technologies, the present invention provides a PC / ASA composite material with high gloss and high mechanical strength, which has excellent mechanical properties and is resistant to light and oxygen aging.

[0006] To achieve the above object, the present invention provides a high-gloss and high-mechanical-strength PC / ASA composite material, comprising the following raw materials in parts by weight: 40 to 60 parts of PC resin 1, 10 to 30 parts of PC resin 2, 5 to 10 parts of ASA rubber powder, 15 to 30 parts of SAN resin, 2 to 9 parts of PMMA resin, 0.1 to 0.5 parts of compound antioxidant, 0.4 to 0.8 parts of lubricant, 0.5 to 1.5 parts of compatibilizer, 2 to 4 parts of SAN carrier black masterbatch, and 0.1 to 0.5 parts of ultraviolet absorber; under the conditions of 300° C. and 1.2 kg load, the melt index of the PC resin 1 is 8 to 14 g / 10 min, and the melt index of the PC resin 2 is 18 to 24 g / 10 min.

[0007] Preferably, the molecular weight of the PC resin 1 is 30,000 to 60,000, and the molecular weight of the PC resin 2 is 10,000 to 30,000.

[0008] Preferably, the mass fraction of acrylic rubber in the ASA rubber powder is 55% to 65%.

[0009] Preferably, at 220° C. and a load of 10 kg, the melt index of the SAN resin is 25 to 35 g / 10 min.

[0010] Preferably, under the conditions of 230° C. and 3.8 kg load, the melt index of the PMMA resin is 10 to 20 g / 10 min.

[0011] Preferably, the compound antioxidant is obtained by compounding a hindered phenol antioxidant and a phosphite antioxidant.

[0012] Preferably, the lubricant includes at least one of PETS and EBS.

[0013] Preferably, the compatibilizer is maleic anhydride grafted SAN.

[0014] Preferably, the ultraviolet absorber is a benzotriazole ultraviolet absorber.

[0015] Preferably, the carbon black content of the SAN carrier black masterbatch is 40% to 50% by mass.

[0016] To achieve the above object, the present invention also provides a method for preparing a high-strength, optically transparent dealcoholized organic silicon sealant, comprising the following steps:

[0017] Step 1: Mix PC resin 1, PC resin 2, ASA rubber powder, SAN resin, PMMA resin, compound antioxidant, lubricant, compatibilizer, SAN carrier black masterbatch and UV absorber in a blender.

[0018] Step 2: adding the mixed raw materials to a twin-screw extruder for extrusion, cooling, granulation and drying; the barrel of the twin-screw extruder is 200-250° C., and the screw speed of the twin-screw extruder is 220-600 rpm.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The main components of the PC / ASA composite material of the present invention are PC resin 1 and PC resin 2. Under the conditions of 300°C and 1.2kg load, the melt index of PC resin 1 is 8-14g / 10min, and the fluidity is relatively low, but its molecular weight is relatively large, and it has excellent impact resistance and heat resistance, so that the composite material has excellent impact resistance and heat resistance. Due to the high content of PC resin 1 in the composite material and the low fluidity of PC resin 1, the surface of the composite material injection molded product has uneven pitting. In order to improve the above-mentioned undesirable situation, PC resin 2 is added to the composite material, which can be well melted with PC resin 1. Under the conditions of 300°C and 1.2kg load, the melt index of PC resin 2 is 18-24g / 10min, and the fluidity is relatively high, which improves the fluidity of the composite material during injection molding and reduces the unevenness of the product surface.

[0021] 2. ASA rubber powder, PMMA resin and SAN resin are added to the composite material. The synergistic effect of ASA rubber powder, PMMA resin and SAN resin makes the PC / ASA composite material have the effects of high gloss black and high gloss surface.

[0022] 3. Adding SAN resin and compatibilizer into PC / ASA composite material improves the compatibility between the components of PC / ASA composite material, making PC / ASA composite material more stable.

[0023] 4. PC / ASA composite materials are added with UV absorbers, so that PC / ASA composite materials can be exposed to light outdoors for a long time and are not easy to age. PC / ASA composite materials are added with compound antioxidants to further improve the material's antioxidant properties and extend its service life.

[0024] 5. The PC / ASA composite material of the present invention is used for injection molding of automobile exterior parts, which are resistant to light and oxygen aging; and have a high-gloss black and high-gloss appearance that can meet the visual needs of customers; the automobile exterior parts also have good mechanical properties, so that the automobile exterior parts are not easily deformed and damaged due to stress. DETAILED DESCRIPTION

[0025] The features of the present invention and other related features are further described in detail below through embodiments to facilitate understanding by those skilled in the art:

[0026] An embodiment of the present invention provides a high-gloss, high-mechanical-strength PC / ASA composite material, comprising the following raw materials in parts by mass: 40 to 60 parts of PC resin 1, 10 to 30 parts of PC resin 2, 5 to 10 parts of ASA rubber powder, 15 to 30 parts of SAN resin, 2 to 9 parts of PMMA resin, 0.1 to 0.5 parts of compound antioxidant, 0.4 to 0.8 parts of lubricant, 0.5 to 1.5 parts of compatibilizer, 2 to 4 parts of SAN carrier black masterbatch, and 0.1 to 0.5 parts of ultraviolet absorber; under the conditions of 300° C. and 1.2 kg load, the melt index of the PC resin 1 is 8 to 14 g / 10 min, and the melt index of the PC resin 2 is 18 to 24 g / 10 min.

[0027] In some embodiments, the molecular weight of the PC resin 1 is 30,000 to 60,000, which is relatively large and has excellent impact resistance and heat resistance, so that the composite material has excellent impact resistance and heat resistance.

[0028] In some embodiments, the PC resin 2 has a molecular weight of 10,000 to 30,000 and has high fluidity, which improves the fluidity of the composite material during injection molding and reduces the unevenness of the product surface.

[0029] In some embodiments, the mass fraction of the acrylic rubber in the ASA rubber powder is 55% to 65%. The ASA rubber powder has excellent weather resistance and glossiness, and can improve the overall glossiness of the composite material.

[0030] In some embodiments, under the conditions of 220° C. and 10 kg load, the melt index of the SAN resin is 25 to 35 g / 10 min. The lubricant includes at least one of PETS and EBS. The SAN resin and the compatibilizer are added to the composite material to improve the compatibility between the components of the PC / ASA composite material, making the PC / ASA composite material more stable. In addition, the SAN resin can also improve the gloss and impact resistance of the PC / ASA composite material.

[0031] In some embodiments, under the conditions of 230° C. and 3.8 kg load, the melt index of the PMMA resin is 10 to 20 g / 10 min. The PMMA resin can improve the wear resistance of the PC / ASA composite material.

[0032] In some embodiments, the compound antioxidant is obtained by compounding a hindered phenol antioxidant and a phosphite antioxidant, so that the PC / ASA composite material can be exposed to light outdoors for a long time and may not be easily aged.

[0033] In some embodiments, in some embodiments, the compatibilizer is maleic anhydride grafted SAN, which improves the compatibility between the components of the PC / ASA composite material, making the PC / ASA composite material more stable.

[0034] In some embodiments, the carbon black content of the SAN carrier black masterbatch is 40% to 50% by mass, which is well compatible with the components of the PC / ASA composite material, and the carbon black content is relatively high, making the PC / ASA composite material bright black in appearance.

[0035] The embodiment of the present invention also provides a method for preparing a high-gloss, high-mechanical-strength PC / ASA composite material, comprising the following steps:

[0036] Step 1: Mix 40-60 parts of PC resin 1, 10-30 parts of PC resin 2, 5-10 parts of ASA rubber powder, 15-30 parts of SAN resin, 2-9 parts of PMMA resin, 0.1-0.5 parts of compound antioxidant, 0.4-0.8 parts of lubricant, 0.5-1.5 parts of compatibilizer, 2-4 parts of SAN carrier black masterbatch and 0.1-0.5 parts of ultraviolet absorber in a blender.

[0037] Step 2: adding the mixed raw materials to a twin-screw extruder for extrusion, cooling, granulation and drying; the barrel of the twin-screw extruder is 200-250° C., and the screw speed of the twin-screw extruder is 220-600 rpm.

[0038] In some embodiments, the feeding speed of the twin-screw extruder is 12 to 24 rpm.

[0039] In some embodiments, in step 1, the raw materials of the PC / ASA composite material need to be dried at 80-100° C. for 1-2 hours to remove the volatile substances.

[0040] In some embodiments, in step 1, the rotation speed of the stirrer is 400 to 800 rpm, and the stirring time is 6 to 10 minutes.

[0041] Example 1

[0042] A method for preparing a high-gloss, high-mechanical-strength PC / ASA composite material comprises the following steps:

[0043] Step 1: Dry 50 parts of PC resin 1, 15 parts of PC resin 2, 5 parts of ASA rubber powder, 23 parts of SAN resin, 5 parts of PMMA resin, 0.2 parts of compound antioxidant, 0.5 parts of PETS (lubricant), 1 part of compatibilizer, 3.5 parts of SAN carrier black masterbatch, and 0.3 parts of ultraviolet absorber at 90°C for 2 hours, then put them into a mixer and stir for 10 minutes at a speed of 600 rpm.

[0044] Step 2: Add the mixed raw materials to a twin-screw extruder for extrusion, cooling, granulation and drying; the 11 temperature zones of the twin-screw extruder are set to 200°C, 250°C, 250°C, 245°C, 245°C, 245°C, 245°C, 250°C, 250°C, respectively. The feeding speed of the twin-screw extruder is 15 rpm, and the screw speed of the twin-screw extruder is 350 rpm.

[0045] Examples 2 to 4 and Comparative Examples 1 to 4: The raw material formula was changed according to Table 1, and the PC / ASA composite materials of Examples 2 to 4 and Comparative Examples 1 to 4 were prepared according to the preparation method of Example 1.

[0046] Table 1 Formulas of Examples 1 to 4 and Comparative Examples 1 to 4

[0047]

[0048] The PC resin 1 selected in the above embodiments and comparative examples is 2100 powder from Wanhua Chemical Group Co., Ltd., with a molecular weight of 50,000. PC resin 2 is 2220 powder from Wanhua Chemical Group Co., Ltd., with a molecular weight of 30,000. ASA rubber powder is A600N from Techno-UMG Co., Ltd. SAN resin is 80HF from LG Chemical Enterprise Co., Ltd. PMMA resin is SF01 from Wanhua Chemical Group Co., Ltd. The compounded antioxidant is a compound of models 1076 and 168 in a mass fraction of 1:1. PETS is from Lonza Group, USA. The compatibilizer is SMA-725 from Shanghai Huawen Electronic New Materials Co., Ltd. The SAN carrier black masterbatch is CB5093 from MUIL Chemical Co., Ltd. The ultraviolet absorber is from UV-234.

[0049] The PC / ASA composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were subjected to the following tests.

[0050] 1. Test the melt index of PC / ASA composite material at 260℃ and 5kg load.

[0051] 2. Determine the tensile strength of PC / ASA composite materials according to ASTM D638 standard.

[0052] 3. Determine the flexural strength and flexural modulus of PC / ASA composite materials according to ASTM D790 standard.

[0053] 4. The notched impact strength of PC / ASA composites was determined according to ASTM D256-2010.

[0054] 5. Use D65 light source to measure the blackness of PC / ASA composite materials.

[0055] 6. Observe the pitting on the surface of PC / ASA composite material.

[0056] Table 2 Test results of Examples 1 to 4 and Comparative Examples 1 to 4

[0057]

[0058] (1) From the data in Table 2, it can be seen that the tensile strength, flexural strength and notched impact strength of the PC / ASA composite materials of Examples 1 to 4 are better than those of Comparative Example 2. This is because PC resin 1, as the main body of the composite material, has low fluidity, high molecular weight, and excellent impact resistance, which can improve the mechanical properties of the composite material. PC resin 2 has high fluidity but relatively poor impact resistance. Increasing the content of PC resin 2 in the composite material will reduce its mechanical properties.

[0059] (2) By comparing Examples 1 and 4 with Comparative Example 2, it can be seen that the higher the content of PC resin 1 in the composite material, the lower the content of PC resin 2, and the more uneven pitting there is on the surface of the composite material. This is because the PC resin 1 has a low melt index and poor fluidity during injection molding, resulting in uneven pitting on the surface of the composite material, affecting the appearance quality of the material. In order to balance the composite material with good mechanical properties and smooth appearance, the optimal mass ratio of PC resin 1 to PC resin 2 is 45-55:15-20.

[0060] (3) By comparing Example 1 and Example 2, it can be seen that although the mass fraction of PC resin 1 in Example 1 is higher than that in Example 2, the number of pitting on the surface of the composite material of Example 1 is still less than that of Example 2. This is because the SAN resin and PMMA resin increase the fluidity of the composite material and reduce the uneven pitting generated during injection molding.

[0061] (4) By comparing Example 4 with Comparative Examples 1 and 4, it can be seen that PMMA resin can synergize with PC resin 1, ASA rubber powder and SAN resin to improve the mechanical properties of the composite material.

[0062] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structural transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A high gloss, high mechanical strength PC / ASA composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 40 to 60 parts of PC resin 1, 10 to 30 parts of PC resin 2, 5 to 10 parts of ASA rubber powder, 15 to 30 parts of SAN resin, 2 to 9 parts of PMMA resin, 0.1 to 0.5 parts of compound antioxidant, 0.4 to 0.8 parts of lubricant, 0.5 to 1.5 parts of compatibilizer, 2 to 4 parts of SAN carrier black masterbatch, and 0.1 to 0.5 parts of ultraviolet absorber; under the conditions of 300° C. and 1.2 kg load, the melt index of the PC resin 1 is 8 to 14 g / 10 min, and the melt index of the PC resin 2 is 18 to 24 g / 10 min.

2. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The mass fraction of the acrylic rubber in the ASA rubber powder is 55% to 65%.

3. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: Under the conditions of 220° C. and 10 kg load, the melt index of the SAN resin is 25-35 g / 10 min.

4. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: Under the conditions of 230° C. and 3.8 kg load, the melt index of the PMMA resin is 10 to 20 g / 10 min.

5. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The compound antioxidant is obtained by compounding a hindered phenol antioxidant and a phosphite antioxidant.

6. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The lubricant includes at least one of PETS and EBS.

7. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted SAN.

8. The high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The ultraviolet absorber is preferably a benzotriazole ultraviolet absorber.

9. A high gloss, high mechanical strength PC / ASA composite material according to claim 1, characterized in that: The carbon black content of the SAN carrier black masterbatch is 40% to 50% by mass.

10. A method for preparing a high gloss, high mechanical strength PC / ASA composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Mix PC resin 1, PC resin 2, ASA rubber powder, SAN resin, PMMA resin, compound antioxidant, lubricant, compatibilizer, SAN carrier black masterbatch, and ultraviolet absorber in a mixer; Step 2: adding the mixed raw materials to a twin-screw extruder for extrusion, cooling, granulation and drying; the barrel of the twin-screw extruder is 200-250° C., and the screw speed of the twin-screw extruder is 220-600 rpm.

Citation Information

Patent Citations

  • Scratch-resistant high-gloss spraying-free PC / ASA alloy material and preparation method thereof

    CN105885379A

  • High-heat-resistance electroplating-free PC / ASA alloy material for vehicle heat dissipation grid

    CN111675892A

  • High-fluidity and scratch-resistant TPV material as well as preparation method and application thereof

    CN112795105A

  • Conductive PC composite material enabling molded product to have surface conductivity and cross section conductivity simultaneously and preparation method of conductive PC composite material

    CN115141476A

  • Spraying-free PC / PMMA composite material with high heat resistance, high weather resistance and high bright black, and preparation method and application thereof

    CN117343522A